PERCOBAAN PEMBUATAN LAK KUNING DENGAN PROSES PELARUTAN - Abdul Hakim Lukman; Toga Silitonga (Jurnal Penelitian Hasil Hutan, 1988)
Shellac  can  be produced   by two different procedures,  namely  heat process  and solvent process:  Ordinarily, domestic shellac produced by heat process,  while imported  one (from  India)  by solvent process.  Solvent  process  yields shellac much purer  than heat processed,  with  relatively  better properties.The physicochemical   properties  of shellac produced   in this experiment,   i.e.:  moisture  content 2. 36%, ash content 0.15%, matter  soluble  in water  0.43%, matter soluble in cold  alcohol  97.86%,  acid number  46.81 and Iod number  16.39. Shellac  from   fabric  manufacturing   have  its properties i.e.: moisture  content  4.03%,  ash content   0.27%,  matter  soluble in water 3.26%,   matter  soluble  in cold alcohol 89.14%, acid number  41.01 and Iod  number  31.35.Result   of  LSD  test  between   experiment   shellac  and  shellac  from  fabric  are reveal highly  significant  different for ash  content,   matter  soluble  in  water,   matter  soluble  in  cold  alcohol  and Iod  number, but  is not  significantly different for  the other properties.